Salam dalam Al-Qur'an dan Budaya Tutur Wong Palembang: Studi Media terhadap Varian Redaksi dan Implementasi Ajaran Qur'ani - Khoiriyyah, Khofawati; Pathur Rahman; Rahmat Hidayat (JOM, 2024)
This research examines the dynamics of greeting perceptions in the Quran and its implementation in the spoken culture of Wong Palembang. The study aims, firstly, to describe the variations in greeting formulations in the spoken culture of Wong Plembang; secondly, to analyze the implementation of Quranic injunctions regarding greetings in the spoken culture of Wong Palembang. Employing a qualitative approach with media study methods, data were collected through discourse analysis of conversation texts and audiovisual documentation related to greeting culture in Palembang. Research instruments included discourse analysis guidelines and observation sheets. Data analysis utilized techniques of meaning and context interpretation. Findings reveal differences in greeting formulations. Palembang society exhibits distinct greeting pronunciations, such as abbreviating phrases like salamlekom, shifting salutation phrases like samlekom, and lekom, and incorporating Palembang's unique phrase assalamualaekom. Greetings in Palembang spoken culture are expressed rapidly. This study contributes significantly to understanding the dynamics of greetings perception in the Quran and its local cultural implementation. It also highlights the uniqueness of Palembang's spoken culture in greeting expressions and explores the meaning and implications of humor in Palembang's cultural context.